Sestrin2 Signaling Pathway Regulates Podocyte Biology and Protects against Diabetic Nephropathy - Moein Ala (Journal of Diabetes Research)
Sestrin2 regulates cell homeostasis and is an upstream signaling molecule for several signaling pathways. Sestrin2 leads to AMP-activated protein kinase- (AMPK-) and GTPase-activating protein activity toward Rags (GATOR) 1-mediated inhibition of mammalian target of rapamycin complex 1 (mTORC1), thereby enhancing autophagy. Sestrin2 also improves mitochondrial biogenesis via AMPK/Sirt1/peroxisome proliferator-activated receptor-gamma coactivator 1 alpha (PGC-1α) signaling pathway. Blockade of ribosomal protein synthesis and augmentation of autophagy by Sestrin2 can prevent misfolded protein accumulation and attenuate endoplasmic reticulum (ER) stress. In addition, Sestrin2 enhances P62-mediated autophagic degradation of Keap1 to release nuclear factor erythroid 2-related factor 2 (Nrf2). Nrf2 release by Sestrin2 vigorously potentiates antioxidant defense in diabetic nephropathy. Impaired autophagy and mitochondrial biogenesis, severe oxidative stress, and ER stress are all deeply involved in the development and progression of diabetic nephropathy. It has been shown that Sestrin2 expression is lower in the kidney of animals and patients with diabetic nephropathy. Sestrin2 knockdown aggravated diabetic nephropathy in animal models. In contrast, upregulation of Sestrin2 enhanced autophagy, mitophagy, and mitochondrial biogenesis and suppressed oxidative stress, ER stress, and apoptosis in diabetic nephropathy. Consistently, overexpression of Sestrin2 ameliorated podocyte injury, mesangial proliferation, proteinuria, and renal fibrosis in animal models of diabetic nephropathy. By suppressing transforming growth factor beta (TGF-β)/Smad and Yes-associated protein (YAP)/transcription enhancer factor 1 (TEF1) signaling pathways in experimental models, Sestrin2 hindered epithelial-mesenchymal transition and extracellular matrix accumulation in diabetic kidneys. Moreover, modulation of the downstream molecules of Sestrin2, for instance, augmentation of AMPK or Nrf2 signaling and inhibition of mTORC1, has been protective in diabetic nephropathy. Regarding the beneficial effects of Sestrin2 on diabetic nephropathy and its interaction with several signaling molecules, it is worth targeting Sestrin2 in diabetic nephropathy.